2009
DOI: 10.1074/jbc.m807930200
|View full text |Cite
|
Sign up to set email alerts
|

BMP4-Smad Signaling Pathway Mediates Adriamycin-induced Premature Senescence in Lung Cancer Cells

Abstract: Cell senescence, an irreversible cell cycle arrest, reflects a safeguard program that limits the capacity of uncontrolled cell proliferation. Treatment of tumor cells with certain chemotherapeutic agents activates premature senescence to decrease the tumorigenecity. Here we show that sublethal concentrations of adriamycin could induce premature senescence in lung cancer cells. Adriamycin treatment resulted in the up-regulation of BMP4, which is underexpressed in NSCLC (non-small cell lung cancers). Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…Now the evaluation of the different BMP signaling pathways revealed that the canonical SMAD1/5/8 pathway is indeed activated in these breast cancer cell lines after BMP4 treatment. Most of the previous studies, for example in pancreatic, lung, and colorectal cancer, also show that BMP4 typically signals through the SMAD pathway [21,34,39,40,50,54]. None of the studied cell lines showed activation of MAP kinases ERK1/2 or p38 in response to BMP4 even though such responses have been reported in human mammary epithelial cells [55] and in pancreatic cancer cells [40].…”
Section: Discussionmentioning
confidence: 72%
“…Now the evaluation of the different BMP signaling pathways revealed that the canonical SMAD1/5/8 pathway is indeed activated in these breast cancer cell lines after BMP4 treatment. Most of the previous studies, for example in pancreatic, lung, and colorectal cancer, also show that BMP4 typically signals through the SMAD pathway [21,34,39,40,50,54]. None of the studied cell lines showed activation of MAP kinases ERK1/2 or p38 in response to BMP4 even though such responses have been reported in human mammary epithelial cells [55] and in pancreatic cancer cells [40].…”
Section: Discussionmentioning
confidence: 72%
“…While the role of BMP4 in aging is less understood, some reports have indicated that BMP4 is an important mediator of atrophic age-related macular degeneration because it mediates oxidative stress-induced retinal pigment epithelium senescence in vitro via the SMAD and p38 pathways ). In addition, overexpression of BMP4 was able to induce premature senescence in lung cancer cells (Su et al 2009). The role of Biogerontology (2011) 12:293-308 301 BMP4 in epigenetic regulation and in IUGR is also not well understood, but a recent article by Murohashi et al (2010) showed that trophoblast cells produce BMP4 by means of CDX2 to promote the proper growth of early mouse embryos.…”
Section: A Common Regulatory Pathway For Development and Aging In H mentioning
confidence: 98%
“…We and others have demonstrated that treatment of tumor cells with Adriamycin preferentially induces senescence rather than apoptotic cell death (Chang et al, 1999;Elmore et al, 2002;Su et al, 2009). In addition, previous studies in thyroid cancer and hepatoma cells have demonstrated that Adriamycin can induce autophagy (Lin et al, 2009;Qian and Yang, 2009).…”
Section: Discussionmentioning
confidence: 99%